Spatial detection and localisation of multiple laser beams in optical measuring systems - Ruprecht, Jasmin; Su, Mingshuai; Hoffmann, Maximilian; Ortlepp, Ingo (Technisches Messen, 2025)
Optical instruments are used in a broad range of applications in different fields of research and industry like microscopy, material science, metrology and fabrication. There, the optical adjustment of laser beams, optical rays and optical axes to a certain position is crucial for the correct function of the overall system. Often, multiple axes have to be adjusted, which requires the monitoring of multiple rays, preferably simultaneously. In this paper, a method for the spatial localisation of multiple laser beams is presented and demonstrated for an application in precision dimensional metrology. There, the position of seven spatially distributed laser beams can be detected with an uncertainty of <10 μm, enhancing the accuracy of the overall system. The underlying method is flexible in its approach and can be adapted to other optical systems.
CRIS-Team Scopus Importer:2025-01-31
Keywords: adjustment; laser beam; nanomeasurement; nanopositioning; optical detection; optical sensors